Research Model of the Qur'an and Hadith - Muhammad Wafiuddin Asyraf; Achmad Sulton (Tilawah: Journal of Al-Qur'an Studies, 2026)
Research on the Qur'an and Hadith is the primary foundation for the development of Islamic studies. Over time, research models on these two primary sources of Islam have undergone a methodological transformation, from traditional, history-based approaches to contextual, interdisciplinary approaches. This article aims to comprehensively examine research models on the Qur'an and Hadith, both classical and modern, and their relevance in addressing contemporary challenges. This research uses a qualitative approach based on library research. The results indicate that research models on the Qur'an and Hadith are dynamic and adaptive to developments in science, without abandoning the principles of textual authenticity.